Uji Sensitivitas Bakteri Probiotik Terhadap Vibrio harveyi Penyebab Vibriosis Secara In Vitro - Zaraswati Dwyana; Murniati Murniati (Jurnal Ilmu Alam dan Lingkungan, 2020)
The purpose of this study was to determine the sensitivity of probiotic bacteria Bacillus sp, Photobacterium sp and Lactobacillus sp and combination of them for inhibiting the growth of V. harveyi. Sensitivity is known by measuring the diameter of the barrier formed by probiotic bacteria against V. harveyi using agar diffusion method on the Mueller Hinton Agar (MHA) medium with an incubation period of 24 hours at 300C. A seven treatment of a combination of probiotic bacteria was used. The study was arranged in a Completely Randomized Design (CRD) in 3 replications. The observational data were analyzed by analysis of variance then continued with Duncan's Real Distance Test. The results showed that the treatment for the combination of Bacillus sp with Lactobacillus sp was the best for inhibiting the growth of V.harveyi causing vibriosis.